Copper-based corrosion-resistant flux-cored wire for dredging pipeline, preparation method and application method

CN122875985APending Publication Date: 2026-10-09JIANGSU JUXIN PETROLEUM STEEL PIPE
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611362437.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-03
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

现有焊接材料普遍存在耐海水腐蚀性能不足、焊缝组织不均匀、耐点蚀能力差以及焊接接头长期服役稳定性不足等问题

Benefits of technology

[0022]本发明中的Ni、Sn、Mo及Cr协同作用提高焊缝耐海水腐蚀性能和抗点蚀能力;La2O3能够净化熔池并细化晶粒,提高焊缝组织均匀性和致密性。采用本发明药芯焊丝获得的焊接接头组织均匀、界面结合良好、耐腐蚀性能优异,适用于疏浚管道、海洋工程装备、海水输送系统及其他腐蚀环境构件的焊接与修复。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122875985A_ABST
    Figure CN122875985A_ABST
Patent Text Reader

Abstract

The application discloses a copper-based corrosion-resistant flux-cored wire for dredging pipes, a preparation method and an application method, the flux-cored wire comprises a core and a sheath; the core comprises the following components in percentage by mass: Ni powder 15-25%, Sn powder 5-10%, Mo powder 1-5%, Cr powder 1-5%, La2O3 powder 0.5-2% and the balance of copper powder, and the sum of the percentage by mass of the components is 100%. The flux-cored wire is prepared through powder mixing, filling, closed forming and multi-pass drawing, and welding is carried out by adopting shielded metal arc welding. The Ni, Sn, Mo and Cr in the application have a synergistic effect to improve the seawater corrosion resistance and pitting resistance of the weld; La2O3 can purify the molten pool and refine the grains, and improve the uniformity and compactness of the weld structure. The welding joint obtained by adopting the flux-cored wire has uniform structure, good interface bonding and excellent corrosion resistance, and is suitable for the welding and repair of dredging pipes, marine engineering equipment, seawater conveying systems and other components in corrosive environments.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of welding materials and surface engineering technology, and in particular to a copper-based corrosion-resistant flux-cored welding wire for dredging pipelines, its preparation method and application method. Background Technology

[0002] Dredging is an important component of port construction, waterway maintenance, coastal management, and marine resource development. Dredging pipelines, as key equipment for transporting mixed media of mud, sand, and seawater, operate in a complex environment. They are subjected not only to long-term corrosion from chloride-containing seawater but also to scouring and abrasion from mud and sand particles, making them highly susceptible to corrosion failure, wear and thinning, and damage to welded joints.

[0003] Currently, dredged pipelines are generally manufactured using low-alloy steel or carbon steel. While these materials offer high strength and low manufacturing costs, their resistance to seawater corrosion is relatively poor. Particularly in welded joint areas, the thermal cycle during welding alters the microstructure and composition, easily creating electrochemically sensitive corrosion zones. Under the influence of seawater, these zones exhibit pitting corrosion, crevice corrosion, and localized corrosion, severely impacting the pipeline's service life and operational safety.

[0004] Copper-based alloys are widely used in shipbuilding, marine engineering, and seawater transport systems due to their excellent resistance to seawater corrosion, good thermal conductivity, and high resistance to biofouling. Using copper-based welding materials for welding or surface strengthening of pipe joints can effectively improve the corrosion resistance of the welded joints. However, traditional copper-based solid welding wires suffer from difficulties in adjusting alloy composition, high production costs, and limitations in the addition of strengthening elements, making it difficult to meet the comprehensive performance requirements of welded joints in complex marine environments.

[0005] Currently, there are relatively few specialized copper-based corrosion-resistant flux-cored welding wires developed for the service environment of welded joints in dredged pipelines. Existing welding materials generally suffer from insufficient resistance to seawater corrosion, uneven weld microstructure, poor resistance to pitting corrosion, and insufficient long-term service stability of welded joints. Furthermore, some flux-cored welding wires contain a large amount of slag-forming agents, resulting in excessive slag during welding, which is detrimental to continuous automated welding operations and affects construction efficiency.

[0006] Therefore, developing a copper-based corrosion-resistant flux-cored welding wire suitable for welded joints of dredged pipelines and establishing a matching welding process, so that the welded joints simultaneously possess excellent seawater corrosion resistance, good mechanical properties, and high welding quality, has significant engineering application value for improving the service life of dredged pipelines, reducing maintenance costs, and ensuring the safe operation of the project. Summary of the Invention

[0007] The purpose of this invention is to overcome the shortcomings of existing technologies and provide a copper-based corrosion-resistant flux-cored welding wire for dredging pipelines, its preparation method, and its application method. By rationally designing the flux core composition, the cladding layer exhibits excellent seawater corrosion resistance, erosion wear resistance, and good interfacial bonding performance, meeting the long-term service requirements of welded joints in dredging pipelines.

[0008] The technical solution of the present invention is: a copper-based corrosion-resistant flux-cored welding wire for dredging pipelines, comprising an outer sheath and a flux core, wherein the flux core comprises the following components by mass percentage: Ni powder: 15% to 25%, Sn powder: 5% to 10%, Mo powder: 1% to 5%, Cr powder: 1% to 5%, La2O3 powder: 0.5% to 2%, and the balance being copper powder, wherein the sum of the mass percentages of the above components is 100%.

[0009] Preferably: Ni powder: 20%; Sn powder: 8%; Mo powder: 3%; Cr powder: 3%; La2O3 powder: 1%; the balance is copper powder.

[0010] The thickness of the pure copper strip is 0.2-0.4 mm.

[0011] The width of the pure copper strip is 6-8mm.

[0012] The flux-cored wire has a flux-cored filling rate of 20wt%-23wt%.

[0013] The diameter of the flux-cored welding wire is 1.0-1.4 mm.

[0014] A method for preparing copper-based corrosion-resistant flux-cored welding wire for dredging pipelines includes the following steps: S1. Weigh the above powder materials according to the mass percentage; S2. Mix the weighed powder evenly in a powder mixer; S3. Roll the pure copper strip into a U-shaped groove, fill the U-shaped groove with the mixed core powder and control the filling rate; S4. Close and roll the filled U-shaped groove to form a tubular welding wire blank, and then draw it to reduce the diameter to the predetermined diameter; S5. Straighten and coil the drawn welding wire to obtain flux-cored welding wire.

[0015] In step S2, a V-type powder mixer is used for powder mixing; the speed of the powder mixer is 300-500 r / min; and the mixing time is 2-4 h.

[0016] In step S4, the drawing diameter reduction speed is 0.5-1.5 m / min; multiple passes are used for gradual diameter reduction, with each reduction being 0.1-0.3 mm, until the final diameter reaches 1.0-1.4 mm.

[0017] In step S4, during the drawing and diameter reduction process, the surface of the welding wire is periodically wiped with acetone or anhydrous ethanol to remove oil stains; in step S6, the straightening is performed using a wire drawing machine, and the winding and packaging is performed using vacuum packaging or inert gas filling packaging.

[0018] The application method of copper-based corrosion-resistant flux-cored welding wire for dredging pipelines includes the following steps: Step 1: Clean the substrate surface to remove the oxide scale.

[0019] Step 2: Preheat the cleaned substrate to the predetermined temperature; Step 3: Using gas metal arc welding (GMAW), the flux-cored wire is welded and clad in multiple layers on the substrate surface in an adjacent lap joint manner under a protective gas atmosphere. Step 4: After the cladding is completed, allow it to cool naturally.

[0020] In step 3, the welding current is 180-220A; the welding voltage is 20-25V; the welding speed is 0.3-0.6m / min; and the wire feed speed is 4.0-6.0m / min.

[0021] In step 3, the shielding gas is 80% Ar and 20% CO2; the shielding gas flow rate is 15-20 L / min; the overlap rate of adjacent weld passes is 55%-65%; and the interpass temperature is controlled at 150-200℃.

[0022] In this invention, the synergistic effect of Ni, Sn, Mo, and Cr improves the weld's resistance to seawater corrosion and pitting corrosion; La2O3 purifies the molten pool and refines the grains, improving the uniformity and density of the weld microstructure. The welded joints obtained using the flux-cored wire of this invention exhibit uniform microstructure, good interfacial bonding, and excellent corrosion resistance, making them suitable for welding and repairing components in dredging pipelines, marine engineering equipment, seawater transport systems, and other corrosive environments. Attached Figure Description

[0023] Figure 1 This is a metallographic microstructure image of the weld seam after welding with the copper-based corrosion-resistant flux-cored wire in Embodiment 6 of the present invention. Detailed Implementation Example 1

[0024] The copper-based corrosion-resistant flux-cored welding wire for dredging pipelines provided in this embodiment includes a flux core and an outer sheath. The flux core comprises the following components by weight percentage: Ni powder: 15%; Sn powder: 5%; Mo powder: 1%; Cr powder: 1%; La2O3 powder: 0.5%; the balance being copper powder; the sum of the weight percentages of the above components is 100%. The outer sheath is made of pure copper strip. The thickness of the pure copper strip is 0.3 mm. The width of the pure copper strip is 7 mm. The flux filling rate in the flux-cored wire is 20 wt%. The diameter of the flux-cored wire is 1.2 mm.

[0025] Ni (Ni): Ni can form a continuous solid solution with Cu, which improves the strength and structural stability of the copper matrix; at the same time, it improves the weld metal's resistance to seawater corrosion and pitting corrosion.

[0026] Sn (tin): Sn can form Cu-Sn solid solution, which improves the hardness and corrosion resistance of copper matrix and enhances the stability of passivation film on welded joint surface.

[0027] Mo (Mo): Mo can improve the resistance of weld metal to localized corrosion and enhance its resistance to pitting and crevice corrosion.

[0028] Cr (chromium): Cr can promote the formation of a stable and dense passivation film, and improve the resistance of the weld structure to electrochemical corrosion.

[0029] Mo and Cr form a synergistic effect with the copper matrix, which helps to improve the seawater corrosion resistance of the cladding layer.

[0030] La2O3 (lanthanum oxide): La2O3 can purify the molten pool, refine the grains, and improve the uniformity of the weld structure.

[0031] Residual copper powder: As the main material of the flux core, it ensures that the weld maintains excellent thermal conductivity and corrosion resistance.

[0032] This invention improves the corrosion resistance and structural stability of the cladding layer by synergistic design of multiple elements including Ni, Sn, Mo, Cr and La2O3, while ensuring the good electrical and thermal conductivity of copper-based materials. Example 2

[0033] The method for preparing copper-based corrosion-resistant flux-cored welding wire for dredging pipelines provided in this embodiment includes the following steps: Step S1: Weigh the following powders according to their mass percentages: Ni powder: 15%; Sn powder: 5%; Mo powder: 1%; Cr powder: 1%; La2O3 powder: 0.5%; the remainder is copper powder. Step S2: Mix the weighed powder evenly in a powder mixer to ensure that all components, especially metal powder and ceramic powder with large density differences, can be mixed evenly and avoid component segregation. Step S3: Roll the pure copper strip into a U-shaped groove, fill the U-shaped groove with the mixed core powder and control the filling rate; Step S4: Close and roll the filled U-shaped groove to form a tubular welding wire blank, and then draw it to reduce the diameter to the predetermined diameter; Step S5: Straighten and coil the drawn welding wire to obtain flux-cored welding wire.

[0034] In step S2, the powder mixer is a V-type powder mixer; the powder mixer speed is 300-500 r / min; the powder mixing time is 2-4 h.

[0035] In step S3, the pure copper strip has a thickness of 0.2-0.4 mm, a width of 6-8 mm, and a fill rate of 20wt%-23wt%.

[0036] In step S4, the drawing diameter reduction speed is 0.5-1.5 m / min; multi-pass step-by-step diameter reduction is adopted; each reduction is 0.1-0.3 mm; the final diameter reaches 1.0-1.4 mm; during the drawing process, the surface of the welding wire is wiped with acetone or anhydrous ethanol periodically.

[0037] In step S5, a wire drawing machine is used for straightening; the packaging method is vacuum packaging or inert gas filling packaging.

[0038] Step S2 involves thoroughly mixing metal powders of different particle sizes and densities to ensure uniform dispersion, preventing local enrichment or depletion of alloying elements within the flux core. This ensures that alloying elements can stably enter the molten pool during the welding wire melting process, thereby improving the uniformity of the deposited metal composition.

[0039] In steps S3 and S4, a pure copper strip is used as the outer sheath. The mixed flux-cored powder is filled into the U-shaped groove formed by the copper strip, and the final welding wire is obtained through closed forming and multi-pass drawing and diameter reduction. The copper strip sheath structure can ensure stable feeding of the flux-cored powder during welding. At the same time, multi-pass drawing and diameter reduction can improve the dimensional accuracy and structural compactness of the welding wire, avoiding problems such as loose flux-cored powder and unstable wire feeding during use.

[0040] This invention combines core component design, uniform powder mixing, and copper strip coating forming process to produce a copper-based flux-cored welding wire with stable composition, good processing performance, and stable transition of alloying elements during welding, thereby obtaining a corrosion-resistant copper-based cladding layer. Example 3

[0041] This embodiment provides a method for applying copper-based corrosion-resistant flux-cored welding wire for dredging pipelines, including the following steps: Step 1: Clean the surface of the substrate to be welded; use an angle grinder, wire brush, or sandblasting to thoroughly remove oxide scale, oil, rust, and other impurities from the surface to be clad until a metallic luster is exposed. Then, clean the surface with acetone or anhydrous ethanol and allow it to dry, ensuring the cladding area is clean. Step 2: Preheat the cleaned substrate to a predetermined temperature, which is 200-300℃; Step 3: Using gas metal arc welding (GMAW), the flux-cored wire is welded in multiple layers under a protective gas atmosphere using an adjacent overlap method. Step 4: After welding, allow it to cool naturally.

[0042] In step 1, the cleaning process includes: polishing to remove oxide scale and oil stains; cleaning with acetone or anhydrous ethanol; and air drying.

[0043] In step 2, the preheating temperature is 150-250℃.

[0044] In step 3, the protective gas is 80% Ar and 20% CO2; the gas flow rate is 15-20 L / min; the overlap rate between adjacent weld passes is 55%-65%; the welding current is 180-220 A; the welding voltage is 20-25 V; the welding speed is 0.3-0.6 m / min; the wire feed speed is matched with the welding current; and the interpass temperature is controlled at 150-200℃.

[0045] The application method in this invention is a welding process proposed based on the characteristics of the prepared copper-based corrosion-resistant flux-cored wire. By reasonably controlling the welding parameters, the alloying elements in the flux-cored wire can play a full role and obtain a copper-based cladding layer with uniform structure and good bonding.

[0046] Step 1: Clean the surface of the workpiece to be welded to remove oxides, oil and impurities, ensuring good contact between the molten pool and the substrate during welding, and improving the bonding quality between the weld layer and the substrate.

[0047] Step 2 involves preheating the workpiece to reduce the adverse effects caused by differences in the thermal properties of materials during welding, making the welding process more stable and facilitating the formation of a continuous and dense weld layer.

[0048] Step 3 employs gas metal arc welding (GMAW) to ensure stable melting of the flux-cored wire, allowing constituent elements such as Ni, Sn, Mo, Cr, and La2O3 to fully enter the molten pool. This avoids overheating during welding, which could degrade the microstructure. A mixed shielding gas is used to improve welding stability and reduce oxidation caused by contact between the molten pool and air. Multiple welding passes ensure good bonding between weld beads, reducing microstructure inhomogeneity caused by repeated thermal cycles and resulting in a final weld layer with good integrity.

[0049] This invention enables copper-based flux-cored welding wire to form a stable weld layer through the synergistic effect of pre-welding treatment, welding parameters, and welding process control, thereby improving the microstructure uniformity and corrosion resistance of the welded joint. Example 4

[0050] The preparation and application of the copper-based corrosion-resistant flux-cored welding wire for dredging pipelines provided in this embodiment includes the following steps: Step 1: Weigh out the following by mass percentage: Ni powder 15%; Sn powder 5%; Mo powder 1%; Cr powder 1%; La2O3 powder 0.5%; the remainder is copper powder; Step 2: Mixer speed 300 r / min; time 2 hours; Step 3: Filling rate 20wt%; drawing speed 0.5m / min; the rest is the same as in Example 2.

[0051] Step 4: Welding current 180A; voltage 20V; welding speed 0.30m / min; wire feed speed 4.0m / min; arc width 5mm; interpass overlap rate 55%; shielding gas: 80%Ar and 20%CO2; number of layers: 3; interpass temperature control approximately 150℃.

[0052] The weld obtained by this invention has good formation; uniform structure; no cracks or porosity defects were found; after 720 hours of salt spray corrosion test, only a small amount of corrosion products appeared on the weld surface; the interface bonding strength is 420 MPa.

[0053] In this embodiment, the contents of Ni, Sn, Mo, and Cr are at low levels, and the weld microstructure is mainly Cu-Ni solid solution. Ni element improves the stability of the copper matrix microstructure, Sn element improves the matrix strength and corrosion resistance, and small amounts of Mo and Cr promote the formation of an initial passivation film on the weld surface.

[0054] Due to the low addition of alloying elements, the weld microstructure is uniform, the molten pool has good fluidity, and the welding formation performance is excellent, resulting in a good metallurgical bond between the weld and the base metal. After salt spray corrosion, only a small amount of uniform corrosion products appeared on the weld surface, and no obvious pitting corrosion was observed, indicating that the flux-cored welding wire has good resistance to seawater corrosion. Example 5

[0055] The preparation and application of the copper-based corrosion-resistant flux-cored welding wire for dredging pipelines provided in this embodiment includes the following steps: Step 1: Weigh the following by mass percentage: Ni powder 18%; Sn powder 6%; Mo powder 2%; Cr powder 2%; La2O3 powder 0.8%; the remainder is copper powder; Step 2: Mixer speed 350 r / min; time 3 hours; Step 3: Filling rate 20.5wt%; drawing speed 0.8m / min; the rest is the same as in Example 4; Step 4: Welding current 190A; voltage 21V; welding speed 0.40m / min; wire feed speed 4.5m / min; arc width 6mm; interpass overlap rate 58%; number of layers: 3; interpass temperature control approximately 160℃.

[0056] The weld structure obtained by this invention is uniform; the corrosion resistance is improved; the interfacial bonding strength reaches 470MPa; and the corrosion current density is significantly reduced.

[0057] With the increase of Ni, Sn, Mo and Cr content, the solid solubility of alloying elements in the weld microstructure is further improved. Ni and Sn form a stable Cu-Ni-Sn solid solution, which improves the weld strength and microstructure stability; Mo and Cr can improve the stability and integrity of the passivation film.

[0058] Meanwhile, La2O3 purifies the molten pool, reduces inclusion formation, and promotes microstructure refinement. The resulting weld microstructure is more uniform and dense, the corrosion current density is significantly reduced, and the pitting corrosion resistance is further improved. Compared with Example 4, the overall performance of the welded joint in this example is significantly improved. Example 6

[0059] The preparation and application of the copper-based corrosion-resistant flux-cored welding wire for dredging pipelines provided in this embodiment includes the following steps: Step 1: Weigh the following by mass percentage: Ni powder 20%; Sn powder 8%; Mo powder 3%; Cr powder 3%; La2O3 powder 1%; the remainder is copper powder; Step 2: Mixer speed 400 r / min; time 3 hours; Step 3: Filling rate 21wt%; drawing speed 1.0m / min; the rest is the same as in Example 5; Step 4: Welding current 200A; voltage 22V; welding speed 0.45m / min; wire speed 5.0m / min; arc width 6.5mm; interpass overlap rate 60%; shielding gas: 80%Ar and 20%CO2; number of layers: 3; interpass temperature control approximately 170℃.

[0060] The weld microstructure obtained in this embodiment is uniform and dense; the weld and the substrate achieve good metallurgical bonding; no obvious pitting corrosion was found after 1000 hours of neutral salt spray corrosion testing; the interfacial bonding strength reached 520 MPa; and the corrosion resistance is significantly better than that of Embodiments 4 and 5. In this embodiment, Ni, Sn, Mo, and Cr are in an optimal ratio. Ni is fully dissolved in the copper matrix, significantly improving the stability of the weld microstructure; Mo and Cr work synergistically to form a more stable and dense passivation film structure, which can effectively prevent Cl⁻ from diffusing into the substrate.

[0061] Furthermore, La2O3 has a significant grain-refining effect, resulting in a fine and uniform weld microstructure. No obvious pitting was observed on the weld surface after the salt spray corrosion test, indicating a significant improvement in interfacial bonding strength. This demonstrates that this embodiment achieves optimal overall performance by balancing welding process performance, microstructural stability, and corrosion resistance.

[0062] like Figure 1 As shown, a continuous interface bond is formed, exhibiting good metallurgical bonding characteristics. No obvious macroscopic defects such as cracks, pores, and lack of fusion were observed, and the microstructure is relatively uniform. Example 7

[0063] The preparation and application of the copper-based corrosion-resistant flux-cored welding wire for dredging pipelines provided in this embodiment includes the following steps: Step 1: Weigh the following by mass percentage: Ni powder 22%; Sn powder 9%; Mo powder 4%; Cr powder 4%; La2O3 powder 1.2%; the remainder is copper powder; Step 2: Mixer speed 450 r / min; time 3.5 hours; Step 3: Filling rate 22wt%; drawing speed 1.2m / min; the rest is the same as in Example 5; Step 4: Welding current 210A; voltage 23V; welding speed 0.50m / min; wire feed speed 5.5m / min; arc width 7mm; interpass overlap rate 62%; shielding gas: 80%Ar and 20%CO2; number of layers: 3; interpass temperature control approximately 180℃.

[0064] The weld structure obtained in this embodiment is dense; the weld surface is well formed; the amount of corrosion products generated is significantly reduced; no obvious corrosion defects were found after 1200 hours of salt spray corrosion; the interface bonding strength reaches 550 MPa; and the welded joint has excellent seawater corrosion resistance.

[0065] This embodiment further increases the Mo and Cr content. Mo can improve the passivation film repair ability, and Cr can enhance the passivation film stability, thus further enhancing the weld's resistance to localized corrosion.

[0066] The higher Ni content improved the weld metal strength and seawater corrosion resistance. After prolonged salt spray corrosion, corrosion products on the weld surface were significantly reduced, and no obvious corrosion defects were found. This indicates that the high Ni-Mo-Cr system has a significant effect on improving the marine corrosion resistance of welded joints. Example 8

[0067] The preparation and application of the copper-based corrosion-resistant flux-cored welding wire for dredging pipelines provided in this embodiment includes the following steps: Step 1: Weigh the following by mass percentage: Ni powder 23%; Sn powder 9%; Mo powder 4%; Cr powder 4%; La2O3 powder 1.5%; the remainder is copper powder; Step 2: Mixer speed 400 r / min; time 3 hours; Step 3: Filling rate 22wt%; drawing speed 1.0m / min; the rest is the same as in Example 5; Step 4: Welding current 190A; voltage 21.5V; welding speed 0.45m / min; wire feed speed 4.8m / min; arc width 6.5mm; interpass overlap rate 58%; shielding gas: 80%Ar and 20%CO2; number of layers: 3; interpass temperature control approximately 170℃.

[0068] The weld obtained in this embodiment is free of cracks and porosity; has a uniform microstructure; exhibits excellent corrosion resistance; further reduces corrosion current density; and achieves an interfacial bonding strength of 530 MPa; thus meeting the requirements for long-term service in marine engineering.

[0069] In this embodiment, the La2O3 content is appropriately increased. Rare earth oxides can adsorb inclusions and purify the molten pool, reducing porosity and inclusion defects formed during welding. Simultaneously, they promote grain refinement and improve microstructure uniformity.

[0070] Due to the more uniform and dense microstructure, corrosive media are less likely to diffuse along grain boundaries, further improving the corrosion resistance of the weld. This embodiment improves weld microstructure quality and service stability while ensuring good weldability. Example 9

[0071] The preparation and application of the copper-based corrosion-resistant flux-cored welding wire for dredging pipelines provided in this embodiment includes the following steps: Step 1: Weigh the following by mass percentage: Ni powder 25%; Sn powder 10%; Mo powder 5%; Cr powder 5%; La2O3 powder 2%; the remainder is copper powder; Step 2: Mixer speed 450 r / min; time 3.5 hours; Step 3: Filling rate 22.5 wt%; drawing speed 1.2 m / min; the rest is the same as in Example 5; Step 4: Welding current 210A; voltage 23V; welding speed 0.52m / min; wire feed speed 5.5m / min; The arc width is 7.5mm; the inter-pass overlap rate is 62%; the number of layers is 4 (increasing the number of layers to enhance the cladding thickness); the inter-layer temperature is controlled at approximately 180℃.

[0072] In this embodiment, the contents of Ni, Sn, Mo, Cr, and La2O3 all reach the upper limit of the design range. A stable Cu-Ni-Sn solid solution structure is formed in the weld microstructure, and a more complete and dense passivation protective film is established.

[0073] Higher Mo and Cr contents significantly improved the weld's resistance to pitting and crevice corrosion; La2O3 further improved the uniformity and density of the microstructure. No obvious corrosion pits appeared after prolonged salt spray corrosion, and the corrosion current density was the lowest.

[0074] Therefore, this embodiment achieves optimal resistance to seawater corrosion and high interfacial bonding strength, making it suitable for welding repair of dredged pipelines and marine engineering equipment in high salinity, high humidity, and long-term marine service environments.

[0075] The results of the above embodiments show that: The copper-based corrosion-resistant flux-cored welding wire and its application method provided by this invention can stably produce welded joints with uniform microstructure, good interfacial bonding, and excellent corrosion resistance.

[0076] By adjusting the contents of Ni, Sn, Mo, Cr and La2O3, and optimizing welding process parameters, the weld microstructure, corrosion resistance and bonding strength can be synergistically controlled within a certain range to meet the usage requirements of different working conditions such as dredging pipelines, marine engineering equipment and seawater transportation systems.

[0077] Flux-cored welding wires offer advantages such as flexible composition design, high alloy element utilization, high deposition efficiency, and ease of automated welding. By adding corrosion-resistant alloying elements such as Ni, Sn, Mo, and Cr, along with rare earth modifying elements, the microstructure stability and corrosion resistance of the weld joint can be significantly improved. Furthermore, flux-cored welding wires can be designed with multiple alloys to meet different working conditions, offering greater technological advantages compared to solid welding wires.

[0078] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, should be covered within the scope of protection of the present invention.

Claims

1. A copper-based corrosion-resistant flux-cored welding wire for dredging pipelines, characterized in that: It includes a core and an outer sheath; the core comprises the following components by mass percentage: Ni powder 15%–25%; Sn powder 5%–10%; Mo powder 1%–5%; Cr powder 1%–5%; La2O3 powder 0.5%–2%; the balance being copper powder; the sum of the mass percentages of the above components is 100%.

2. The copper-based corrosion-resistant flux-cored welding wire for dredging pipelines according to claim 1, characterized in that: The outer sheath is made of T2 pure copper strip; the thickness of the pure copper strip is 0.2-0.4 mm; and the width is 6-8 mm.

3. The copper-based corrosion-resistant flux-cored welding wire for dredging pipelines according to claim 1, characterized in that: The core filling rate is 20wt% to 23wt%.

4. The method for preparing the copper-based corrosion-resistant flux-cored welding wire for dredging pipelines according to any one of claims 1 to 3, characterized in that, Includes the following steps: S1. Weigh out Ni powder, Sn powder, Mo powder, Cr powder, La2O3 powder and copper powder according to the formula ratio; S2. Mix all the powders thoroughly; S3. Roll the pure copper strip into a U-shaped groove and fill the U-shaped groove with mixed powder; S4. Close the filled copper strip into shape and draw it to reduce its diameter; S5, straightening, coiling and packaging, to obtain copper-based corrosion-resistant flux-cored welding wire.

5. The method for preparing copper-based corrosion-resistant flux-cored welding wire for dredging pipelines according to claim 4, characterized in that: In step S2, a V-type powder mixer is used for powder mixing; the speed of the powder mixer is 300-500 r / min; and the mixing time is 2-4 h.

6. The method for preparing copper-based corrosion-resistant flux-cored welding wire for dredging pipelines according to claim 4, characterized in that: In step S4, the drawing diameter reduction speed is 0.5-1.5 m / min; multiple passes are used for gradual diameter reduction, with each reduction being 0.1-0.3 mm, until the final diameter reaches 1.0-1.4 mm.

7. The method of applying the copper-based corrosion-resistant flux-cored welding wire for dredging pipelines as described in any one of claims 1 to 3, characterized in that, Includes the following steps: Step 1: Clean the surface of the substrate; Step 2: Preheat the substrate; Step 3: Weld using gas metal arc welding (GMAW); Gas metal arc welding is used. Under the protective gas atmosphere, the flux-cored wire is welded and clad in multiple layers on the base material surface by using an adjacent lap method. Step 4: Allow the material to cool naturally after welding.

8. The application method of the copper-based corrosion-resistant flux-cored welding wire for dredging pipelines according to claim 7, characterized in that: In step 3, the welding current is 180-220A; the welding voltage is 20-25V; the welding speed is 0.3-0.6m / min; and the wire feed speed is 4.0-6.0m / min.

9. The application method of the copper-based corrosion-resistant flux-cored welding wire for dredging pipelines according to claim 7, characterized in that: In step 3, the shielding gas is 80% Ar and 20% CO2; the shielding gas flow rate is 15-20 L / min; the overlap rate of adjacent weld passes is 55%-65%; and the interpass temperature is controlled at 150-200℃.